Prototipe Sistem Penampungan Air Otomatis Berbasis IoT dengan Logika Fuzzy untuk Pertanian Cerdas - Adhin Luthfi Indrawan; Oscar Hadikaryana; Subhanjaya Angga Atmaja (Universitas Kebangsaan Republik Indonesia, 2025)
The development of Internet of Things (IoT) technology has brought significant changes to modern agricultural systems, particularly in terms of water efficiency. This research developed a prototype of an IoT-based automatic water storage system capable of adjusting water distribution according to environmental conditions in real time. The system was built using a NodeMCU ESP8266 as a control center and several sensors, including a soil moisture sensor, a rain sensor, an ultrasonic sensor, a temperature and humidity sensor, and a water flow sensor. The integration of these various sensors allows the system to detect land conditions comprehensively. Mamdani fuzzy logic is used as a decision-making method by considering variables such as soil moisture, weather conditions, and temperature. A rule-based system approach is added to provide more flexible decision rules. The sensor readings are processed by a microcontroller and then sent to the Blynk application so farmers can monitor and control the system via smartphone. Test results show that the system can adapt to various conditions. In dry soil with high temperatures, the pump automatically activates until the moisture threshold is reached. Conversely, when rain is detected or the soil is wet, the system delays watering to avoid waste. Water discharge data is also recorded in real time so that water use can be better controlled. This research demonstrates that the integration of IoT and Mamdani fuzzy logic can improve water distribution efficiency, reduce waste, and support smart farming practices. The developed system has the potential to be widely applied to agricultural land to help farmers manage water resources efficiently and sustainably.